Refractive index less than two: photonic nanojets yesterday, today and tomorrow [Invited]; Optical Materials Express; Vol. 7, iss. 6 - Luk’yanchuk B. S. Boris; Paniagua-Domнnguez R. Ramуn; Minin I. V. Igor Vladilenovich; Minin O. V. Oleg Vladilenovich; Wang Z. Zengbo (2017, 2017)
Title screen